A palaeoenvironmental study of uppermost Triassic to Lower Jurassic successions in high-pressure/high-temperature (HPHT) wells from the Central North Sea, UK. (October 2021) - Vieira, Manuel; Jolley, David; Shaw, David
Abstract: High-pressure/high-temperature wells are traditionally very challenging for biostratigraphical analyses. The temperatures achieved cause the organic matter to become highly mature and palynomorphs are altered, to an extent that can make identification extremely challenging. This study compares two wells and shows that the type of drilling bit and the control of drilling parameters can have a positive impact in the palynology recovery. Both wells are studied for palynology and the well with the best drilling parameters yielded generally good recovery, and although the palynomorphs also exhibit a high thermal maturity, it was possible to confidently identify enough palynomorphs to define the age of the penetrated sediments. The biostratigraphy study reveals a Rhaetian – Early Toarcian dataset from a complete stratigraphic succession that wasn't previously recorded in the Central North Sea. A lithostratigraphic unit is yet to be defined to characterise the sediments interpreted in this paper. The ecological analyses, using statistical methods, assessed the temporal and spatial variations in vegetation and palaeoenvironments. They focused on the Early Jurassic and indicate that during this time the landscape was diverse with a variety of habitats occupied by terrestrial plants dominated primarily by swamp and xerophyte types living near the coastal area. Highlights: First comprehensive palynology study using cuttings from an HPHT well. Relation between drilling parameters and fossil recovery optimization. Rhaetian – Lower Jurassic stratigraphic interval not previously recorded in the Central North Sea. Early Jurassic coastal palaeoenvironments revealed by the palynomorph data.